Eksistensi Kearifan Lokal dalam Melestarikan Rokat “Bhuju' Jepara” di Desa Buddagan 1 Pamekasan - Gilang Achmad Marzuki; Conny Dian Sumadi; Moh. Syarif Hidayat (Lembaga Citra Pustaka, 2024)
Rokat Bhuju’ is a long-standing tradition that is deeply rooted in mysticism, where many members of the local community believe in ancestral spirits that can influence their daily lives. Therefore, all villagers are obliged to uphold and preserve the Rokat Bhuju’ tradition to this day. However, the practice has been adapted to fit Islamic values, incorporating the recitation of Surah Yassin and Tahlil. This research focuses on three main aspects: first, the original form of local wisdom in Buddagan 1 Pamekasan hamlet related to the preservation of Rokat Bhuju’ Jepara; second, the process of implementing Rokat Bhuju’ Jepara; and third, the messages conveyed through the tradition in Buddagan 1 Pamekasan hamlet. Data were collected through observation, interview, and documentation. The results showed that: first, the manifestation of local wisdom in preserving Rokat Bhuju’ Jepara includes rituals and dishes that have special meaning. For example, during the ritual, prayers are offered to Allah SWT for protection, asking the ancestors to bless the community with health, safety, abundant harvests, and protection from disasters. Second, during the Rokat Bhuju’ Jepara ceremony, the community brings coffe, food, and market snacks, followed by the recitation of Surah Yassin and Tahlil, and end with a prayer. This ceremony is held every week on Monday night. Third, the messages that can be learned from the local wisdom of Rokat Bhuju’ Jepara is that this tradition should not be abandoned even though in today’s modern society and many do not believe in this tradition. It is better to preserve this tradition so that it can protect and avoid unwanted things and children and grandchildren can know about this tradition.